Spectrophotometric Determination of Molybdenum(VI) as a Ternary Complex with 4-Nitrocatechol and Benzalkonium Chloride - Vidka V. Divarova; Antoaneta Saravanska; Galya Toncheva; Nikolina Milcheva; Vassil B. Delchev; Kiril Gavazov (Molecules, 2022)
A new liquid—liquid extraction system for molybdenum(VI) was studied. It contains 4-nitrocatechol (4NC) as a complexing chromogenic reagent and benzalkonium chloride (BZC) as a source of heavy cations (BZ+), which are prone to form chloroform-extractable ion-association complexes. The optimum conditions for the determination of trace molybdenum(VI) were found: concentrations of 4NC and BZC (7.5 × 10−4 mol dm−3 and 1.9 × 10−4 mol dm−3, respectively), acidity (3.75 × 10−2 mol dm−3 H2SO4), extraction time (3 min), and wavelength (439 nm). The molar absorptivity, limit of detection, and linear working range were 5.5 × 104 dm3 mol−1 cm−1, 5.6 ng cm−3, and 18.6–3100 μg cm−3, respectively. The effect of foreign ions was examined, and the developed procedure was applied to the analysis of synthetic mixtures and real samples (potable waters and steels). The composition of the extracted complex was 1:1:2 (Mo:4NC:BZ). Three possible structures of its anionic part [MoVI(4NC)O2(OH)2]2− were discussed based on optimizations at the B3LYP/3-21G level of theory, and simulated UV/Vis absorption spectra were obtained with the TD Hamiltonian.